UNIVERSAL MAN: The Seven Lives of John Maynard Keynes - Uta, Criatian (Annals of Spiru Haret University. Economic Series, 2016)
John Maynard Keynes was one of the most influential personalities of the twentieth century. It is considered one of the creators of what today we call Macroeconomics. He played an important role during the Bretton Woods Conference in 1944, after which were put up substantial postwar financial institutions such as the World Bank and International Monetary Fund. The economic policy measures he proposed prevailed in the first decades after World War II and saw a revival in recent years due to the financial crisis of 2008-2009. His works on economics have seen many editions and have been translated into most languages.